2019
DOI: 10.1155/2019/4587929
|View full text |Cite
|
Sign up to set email alerts
|

Field Test Investigation of the Pile Jacking Performance for Prefabricated Square Rigid‐Drainage Piles in Saturated Silt Sandy Soils

Abstract: e rigid-drainage pile, designed to accelerate the dissipation of excess pore water pressure around the pile, is a new type of pile that combines the bearing capacity of ordinary rigid piles and the draining capacity of gravel piles. Field tests of these new piles were performed for the first time at a construction site in the new campus of Jiangyin No. 1 High School. Numerous parameters were observed for the test piles in many trials, including the excess pore water pressures, horizontal soil pressures, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…With the increase in seismic acceleration under high seismic intensity, the anti-liquefaction performance of the composite foundation stabilized with stone columns was obvious in shaking table model tests (Qu et al [17]). Wang [18] found that gravel piles reduced the amplitude of the peak pressure, caused by piling, and quickly dissipated the excess pore water pressure in the liquefiable layer. Based on the results of 1 G laboratory-scale shaking table tests, Dinh et al [19] showed that the compaction and drainage effects of gravel piles were the main factors to reduce the liquefaction of the foundation.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in seismic acceleration under high seismic intensity, the anti-liquefaction performance of the composite foundation stabilized with stone columns was obvious in shaking table model tests (Qu et al [17]). Wang [18] found that gravel piles reduced the amplitude of the peak pressure, caused by piling, and quickly dissipated the excess pore water pressure in the liquefiable layer. Based on the results of 1 G laboratory-scale shaking table tests, Dinh et al [19] showed that the compaction and drainage effects of gravel piles were the main factors to reduce the liquefaction of the foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Steel sheet pile cofferdams have been widely used for river and coastal revetments, piers, and other support structures built in the water because of their convenience of installment, cost efficiency, and reusability. Research has been conducted into the applications of steel sheet piles [1][2][3][4]. e problem of corrosion was found in those steel sheet piles exposed to the marine environment [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…PHC pipe piles are widely used in foundation works in civil, municipal, and other projects in China due to the advantages of a high bearing capacity, high construction efficiency, and reliable quality [5][6][7][8]. e hydraulic jacking method is a common technique for pile penetration that has several advantages such as being vibration-free and noise-free during construction [9][10][11][12]. is method is generally used to press a PHC pipe pile into the site soil.…”
Section: Introductionmentioning
confidence: 99%